2015
DOI: 10.1007/s40520-015-0463-8
|View full text |Cite
|
Sign up to set email alerts
|

Tele-health-care in the elderly living in nursing home: the first Sicilian multimodal approach

Abstract: Telemedicine can be considered as an important tool in improving health and quality of life in the elderly living in nursing homes, and potentially reducing healthcare service access, hospitalization, and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 23 publications
3
75
0
1
Order By: Relevance
“…While our focus was not hospital based, only two RCTs were in nursing facilities. 53,79 Observational studies exist 80,81 ; yet, the lack of rigorous studies in older adults has considerable implications as they are sicker and require increased medical assessment and acuity, 77 ultimately leading to increased utilization. Research to evaluate TMed interventions in such facilities is needed.…”
Section: Discussionmentioning
confidence: 99%
“…While our focus was not hospital based, only two RCTs were in nursing facilities. 53,79 Observational studies exist 80,81 ; yet, the lack of rigorous studies in older adults has considerable implications as they are sicker and require increased medical assessment and acuity, 77 ultimately leading to increased utilization. Research to evaluate TMed interventions in such facilities is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies were conducted in the USA, 47,169,176,210,222,227,230,[299][300][301] two in Australia, 203,274 two in New Zealand 166,236 and one in each of Belgium, 54 Canada, 147 Italy, 101 Japan, 250 Singapore, 163 Norway, 160 Taiwan, 177 the Netherlands 56 and the UK. 277 Thirteen randomised studies were included (six individually randomised parallel group trials, two individually randomised crossover trials and five cluster randomised trials), 47,54,101,147,160,177,203,210,230,236,274,277,299 as were 11 non-randomised studies of interventions. 56,161,163,166,168,169,176,222,227,250,300,301 Details of the studies included in this systematic review are shown i...…”
Section: Findings Of Systematic Evidence Synthesismentioning
confidence: 99%
“…Ten studies described digital interventions aimed at influencing mental health and well-being in care home residents. 56,101,132,160,163,169,176,236,250,274 A majority measured symptoms of depression and dementia. They also report on agitation, a set of behaviours associated with emotional distress that impair social functioning and ADL.…”
Section: Studies Investigating the Effectiveness Of Interventions Formentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by De Luca et al [4] has demonstrated that telemedicine can be considered as an important tool in improving health and quality of life in the elderly living in nursing homes, potentially reducing healthcare service access, hospitalization and costs. It also appears that a telehealth system integrated in a local healthcare service may significantly improve elderly persons' behaviour and reduce the caregivers' burden [5].…”
Section: Dear Editormentioning
confidence: 99%